The emerging Pannexin 1 signalome: a new nexus revealed? - Wicki-Stordeur, Leigh E.; Swayne, Leigh Anne (Frontiers in Cellular Neuroscience, 2014)
Pannexins (Panxs) are a family of single-membrane, large-pore ion, and metabolite permeable channels. Of the three Panx proteins, Panx1 has been most extensively studied, and has recently emerged as an exciting, clinically relevant target in many physiological and pathophysiological settings. This channel is widely expressed across various cell and tissue types; however its links to precise signaling pathways are largely unknown. Here we review the current literature surrounding presently identified Panx1–protein interactions, a critical first step to unraveling the Panx1 signalome. First we elucidate the reported associations of Panx1 with other ion channels, receptors, and channel signaling complexes. Further, we highlight recently identified Panx1–cytoskeleton interactions. Finally, we discuss the implications of these protein–protein interactions for Panx1 function in various cell and tissue types, and identify key outstanding questions arising from this work.